Pathologic femur fractures following limb-salvage surgery and radiotherapy for soft tissue sarcomas: They don't heal!. (November 2017) - Michelitsch, Christian; Frima, Herman; Sommer, Christoph; Furrer, Markus
Abstract : Introduction: Combined limb-sparing surgery and radiation therapy are considered the standard of care for soft tissue sarcomas (STS) of the extremities. The correlation between radiation therapy and the risk of post radiation fracture is known but underestimated and can end up in serious long-term complications. Case description: We reviewed the records of 3 patients with pathological femur fracture years after wide local excision of a STS of the proximal lower extremity with postoperative radiation therapy. All patients received more than 50 Gray to the entire femur circumference. No one received perioperative chemotherapy. During surgery, all patients had bone exposure, whereas only one patient had the periosteum stripped. Results and Conclusions: Two patients were female and one male. The median time from surgery/radiation to fracture was 116 months (range, 84 to 156 months). The median age at the time of diagnosis was 66 years (range, 54 to 79 years). All fractures occurred within the radiation treatment field. Two fractures occurred after minimal or no trauma, one fracture occurred after a mountain bike fall. All three fractures 3/3 (100%) developed a non-union. One patient died due to uncontrolled pulmonary metastasis and local recurrent disease. In the second case we had to perform an exarticulation at hip level due to an uncontrolled infected non-union with soft tissue defect despite several surgical revisions. The third patient is still under treatment of his non-union. Take home message: Local control rates after combined therapy for the treatment of soft-tissue sarcomas are high. However, pathologic fractures after radiation therapy pose an extreme challenge in their treatment and may be associated with long-term complications that can cause physical disability and impairment of the quality of life.